2013 IEEE 13th International Conference on Rehabilitation Robotics (ICORR) 2013
DOI: 10.1109/icorr.2013.6650427
|View full text |Cite
|
Sign up to set email alerts
|

PARO robot affects diverse interaction modalities in group sensory therapy for older adults with dementia

Abstract: We evaluated the seal-like robot PARO in the context of multi-sensory behavioral therapy in a local nursing home. Participants were 10 elderly nursing home residents with varying levels of dementia. We report three principle findings from our observations of interactions between the residents, PARO, and a therapist during seven weekly therapy sessions. Firstly, we show PARO provides indirect benefits for users by increasing their activity in particular modalities of social interaction, including visual, verbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
127
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(136 citation statements)
references
References 14 publications
7
127
0
2
Order By: Relevance
“…Past research identified therapeutic benefits emotionally [22, 26], physically [9], behaviourally [28], and socially [9, 21, 23, 24]. The research reported in this paper adds support to these findings for the use of Paro in improving mood, reducing challenging behaviour, and facilitating social interactions.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Past research identified therapeutic benefits emotionally [22, 26], physically [9], behaviourally [28], and socially [9, 21, 23, 24]. The research reported in this paper adds support to these findings for the use of Paro in improving mood, reducing challenging behaviour, and facilitating social interactions.…”
Section: Discussionsupporting
confidence: 68%
“…Reduced loneliness has been identified previously as a benefit of Paro [9, 23] and the observations of participants in this study suggested two main processes in this respect: the establishment of a direct relationship with the robotic seal and its use in facilitating better social connections with others. Isolated and withdrawn residents talked to Paro in a conversational manner and end-of-life residents verbalised their internal world, in both contexts seemingly reducing a sense of being alone.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Other technologies are being specifically developed to target dementia-related deficits. One example is PARO:45 a socially assistive robot seal pup, which has been shown to increase social interactions between patients with dementia in a group therapy session. Another system, BikeAround,46 employs a stationary bike paired with a virtual reality projection of Google Street View to allow patients with dementia to ‘visit’ personally significant locations and, in doing this, tap into their autobiographical memories.…”
Section: Discussionmentioning
confidence: 99%
“…deemed useful to improve positive affect [9] and social interactions and to reduce loneliness [10] [11].…”
Section: Introductionmentioning
confidence: 99%